Sphingomyelin effects in caveolin-1 mediated membrane curvature published as part of the journal of physical chemistry virtual special issue ``computational and experimental advances in biomembranes'' - Krishna, Anjali; Prakash, Shikha; Sengupta, Durba (Journal of Physical Chemistry B, 2020)
The caveolin-1 (cav-1) protein is an integral component of caveolae and has been reported to colocalize with cholesterol and sphingomyelin-rich curved membrane domains. Here, we analyze the molecular interactions between cav-1 and sphingomyelin containing bilayers using a series of coarse-grain simulations, focusing on lipid clustering and membrane curvature. We considered a palmitoylated-cav-1 construct interacting with phospholipid/cholesterol membranes with asymmetrically distributed sphingomyelin, varying between 5 and 15% in total. We observe that cav-1 binds to the intracellular leaflet and induces a small positive curvature in the leaflet to which it is bound and an opposing negative curvature in the extracellular leaflet. Both cholesterol and sphingomyelin are observed to cluster in cav-1 bound membranes, mainly in the extracellular leaflet. Due to their negative spontaneous curvature, clustering of cholesterol and sphingomyelin facilitates membrane curvature such that the extent of either cholesterol or sphingomyelin clustering is dependent on the curvature induced. Our results suggest that cav-1 binding induces concentration-dependent curvature effects in sphingomyelin-rich membranes. Overall, our work is an important step in understanding the molecular basis of curvature and lipid clustering in cav1 bound cellular membranes.